Antimicrobial peptide CAP 18 and its effect on Yersinia ruckeri infections in rainbow trout Oncorhynchus mykiss (Walbaum): comparing administration by injection and oral routes - J K Chettri; F Mehrdana; E B Hansen; A Ebbensgaard; M T Overgaard; A H Lauritsen; I Dalsgaard; K Buchmann (Journal of Fish Diseases, 2017)
The antimicrobial peptide CAP 18 has been demonstrated to have a strong in vitro bactericidal effect on Yersinia ruckeri , but its activity in vivo has not been described. In this work, we investigated whether CAP 18 protects rainbow trout Oncorhynchus mykiss (Walbaum) against enteric red mouth disease caused by this pathogen either following i.p. injection or by oral administration (in feed). It was found that injection of CAP 18 into juvenile rainbow trout before exposure to Y. ruckeri was associated with lowered mortality compared to non‐medicated fish although it was less effective than the conventional antibiotic oxolinic acid. Oral administration of CAP 18 to trout did not prevent infection. The proteolytic effect of secretions on the peptide CAP 18 in the fish gastrointestinal tract is suggested to account for the inferior effect of oral administration.

Slow spontaneous [Ca2+]i oscillations reflect nucleotide release from renal epithelia - C. S. Geyti; E. Odgaard; M. T. Overgaard; M. E. Juul Jensen; J. Leipziger; H. A. Praetorius (Pflügers Archiv - European Journal of Physiology, 2008)